Suitability of Legacy Subsurface Data for Nascent Geoenergy Activities Onshore United Kingdom - Ireland, Mark T.; Brown, Rachel; Wilson, Miles P.; Stretesky, Paul B.; Kingdon, Andrew; Davies, Richard J. (Frontiers in Earth Science, 2021)
The decarbonisation of energy systems to achieve net zero carbon emissions will likely see the rapid development of carbon capture and storage, energy storage in the subsurface and geothermal energy projects. Subsurface data, in particular seismic reflection surveys and borehole data are vital for geoscientists and engineers to carry out comprehensive assessments of both the opportunities and risks for these developments. Their cost of acquisition means that such legacy data are commonly the only mechanism for site selection so biased data distribution must be accommodated. Here, legacy subsurface data from UK onshore hydrocarbon and coal exploration in the UK are collated and reviewed for their suitability for geoenergy activities. We provide a description of the spatial coverage and a chronology of the acquisition of key seismic reflection and borehole data, as well as examine data resolution and limitations. We discuss the implications of spatial variability in subsurface datasets and the associated subsurface uncertainty as this is vitally important to understanding the suitability of data for decision making. We examine societal aspects of data uncertainty and discuss that when the same data are used to communicate subsurface uncertainty and risk, the source of the data should also be considered, especially where data are not easily publicly accessible. Understanding the provenance and quality criteria of data are vitally important for future geoenergy activities and public confidence in subsurface activities. Finally, we ask should there be minimum data collection criterion, such as resolution requirements, ahead of subsurface activities with potentially significant impacts to the environment, economy, and society?